Optimasi Pengelolaan Keuangan Desa Melalui Partisipasi Masyarakat Dalam Pembangunan Infrastruktur - Primus Nuwa, Arnoldus; Pongge, Maria Imakulata; Dima, Enike Tje Yustin (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2025)
Rural infrastructure development requires community involvement as an essential component of participatory and accountable governance. This study analyzes the forms of community participation in Takatunga Village, the factors influencing it, and its relationship with village financial management, particularly the use of Village Funds for infrastructure development. Using a qualitative descriptive approach through interviews, observations, and document analysis, the findings show that participation primarily takes the form of labor contributions during the implementation stage, while involvement in planning and evaluation remains limited. Key barriers include low self-confidence, time constraints due to agricultural activities, and insufficient information dissemination. Although social capital—such as mutual cooperation and trust in local leaders—encourages community engagement, financial management remains top-down, preventing social capital from being integrated into budgeting processes. The study highlights the need to strengthen deliberation forums, improve community budget literacy, and enhance transparency to promote more substantive participation in village infrastructure development.